THE TEST OF BACTERIAL CONTAMINATION ON MEATBALL PRODUCTS IN THE TRADITIONAL MARKET OF MARISA, POHUWATO - Asnita Kamumu; Rita Amini Warastuti; Agusrianto Yusuf (LPPM Universitas Bina Mandiri Gorontalo, 2021)
ABSTRACT Meatball is one of Indonesia's typical meat-based products. It is usually served at a high temperature, moreover, it contains high nutrient due to the high animal nutrient that is necessary for human growth. The current study aims to determine the test of bacterial contamination on meatball that are sold in the traditional market of Marisa, district of Pohuwato. Five meatball samples were taken from five different vendors, and the sample testing was done in the laboratory of the faculty of science, technology, and health on July 13th, 2020. The test included the total plate count microbial pathogens contamination and E. coli bacteria in the meatballs. The data were analyzed descriptively and presented in a tabular to illustrate the total plate count of pathogen contamination and E. coli bacteria in the meatballs. According to SNI 01-3818-1995, the maximum total plate count (ALT) of colonies/g is 0.1x102, and for the E. coli bacteria, the AMP/g is <3.0. As the results. It shows that the total microbes on the meatballs in the traditional markets of Marisa is ranged between 4.5x104 colonies/g to 2.3x105 colonies/g. It also shows that the meatballs still meet the requirement for the counts of microbial colonies, while the most probable number (AMP) of coliform bacteria is still high